Assessment of Vitamin D Status in General Population of Kashmir Valley of Indian Subcontinent - Mudasir Ahmad Bhat; Kafeel Khan; Uzznain Khan; Isbha Nazir (Indian Association of Preventive and Social Medicine, 2022)
Introduction: The prevalence of vitamin D deficiency is reported to be high throughout the world. Overt Vitamin D deficiency manifests as rickets, birth defects and fractures in children. In adults, its manifestations include osteoporosis, osteomalacia, osteoarthritis, chronic muscular pain, increased risk of fractures, several endocrine, cardiovascular, immunological and neurologic disorders, some types of cancers, and depression. Objectives: To assess the Vitamin D status in general population of Kashmir valley by measuring serum 25-hydroxyvitamin D [25 (OH) D] levels. Method: 270 healthy volunteers from differing professions (69 men and 201 non-pregnant/non-lactating women, aged 18-65 years), residing in Kashmir valley were selected for this study. The samples were collected in both summer and winter months. Vitamin D deficiency/insufficiency was defined as a Serum 25 (OH) D concentration of < 30 ng/ml. Results: 222 (82.2%) of the subjects studied had Vitamin D deficiency. 45 of the 69 males and 177 of the 201 females were found to be Vitamin D deficient. The prevalence of vitamin D deficiency ranged from 58 % in the farmers group to 93% in the employee group. Vitamin D deficient subjects had a significantly lower mean weekly exposure to sunlight. Conclusion: The prevalence of Vitamin D deficiency in Kashmir valley is high especially among women. Serum 25(OH) D concentrations are significantly related to sun exposure.